2005
DOI: 10.1556/abot.47.2005.3-4.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of epiphytic diatoms in water quality monitoring of Lake Velence - recommendations and assignments

Abstract: The suitability of benthic diatoms in the biological monitoring program of the water quality of Lake Velence was tested. Diatom indices were calculated with the aid of the software Omnidia based on reed periphyton samples collected between 1988 and 1990, and 1999 to 2004. We have pointed out which indices are appropriate for indicating the water quality changes of Lake Velence. The correlation between the indices IBD, IPS, IDG, and the total nitrogen, total phosphorus content of the water and chlorophyll-a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…The diatom species composition proved to be a valid proxy of the trophic status for the entire phytobenthos assemblage present in the littoral zone of lakes, using existing river indices (Blanco et al 2004;Ács et al 2005) or lake-specific ones (Hofmann 1999;StengerKovács et al 2007). As stones and pebbles are often absent from lakes, collection of samples from emergent macrophytes has been recommended by many authors (Blanco et al 2004;Schaumburg et al 2004b;King et al 2006;Stenger-Kovács et al 2007).…”
Section: Phytobenthosmentioning
confidence: 99%
See 1 more Smart Citation
“…The diatom species composition proved to be a valid proxy of the trophic status for the entire phytobenthos assemblage present in the littoral zone of lakes, using existing river indices (Blanco et al 2004;Ács et al 2005) or lake-specific ones (Hofmann 1999;StengerKovács et al 2007). As stones and pebbles are often absent from lakes, collection of samples from emergent macrophytes has been recommended by many authors (Blanco et al 2004;Schaumburg et al 2004b;King et al 2006;Stenger-Kovács et al 2007).…”
Section: Phytobenthosmentioning
confidence: 99%
“…Most studies using phytobenthos (hereafter related specifically to diatoms) focus in monitoring running waters (Prygiel et al 1999;Prygiel and Haury 2006), but its use in lakes is limited to few works (Hofmann 1999;Blanco et al 2004;Ács et al 2005;Stenger-Kovács et al 2007). Conversely, phytoplankton has been used as a trophic status bioindicator and is involved in indices based on presence/absence, or relating either abundance, biovolume, biomass (Hörnström 1981, Rosén 1981, Rott 1984, Brettum 1989and Willén 2000in Dokulil 2003, indicator species (Lepistö et al 2004) and functional groups (Padisák et al 2006).…”
mentioning
confidence: 99%
“…Corresponding author: danafidlerova@azet.sk diatoms proved to serve as valuable indicators also in standing waters in many European regions, especially with regard to eutrophication (Hofmann, 1994;King et al, 2000;Kitner and Poulíčková, 2003;Blanco et al, 2004;Poulíčková et al, 2004;Schaumburg et al, 2004;Ács et al, 2005;Stenger-Kovács et al, 2007;Jüttner et al, 2010;Novais et al, 2012;Bennion et al, 2014;Cantonati and Lowe, 2014;De Nicola and Kelly, 2014;Kelly et al, 2014a;Poulíčková et al, 2014). Despite their promising bioindicative potential in European lentic ecosystems, only a few countries have produced diatom-based WFD-compliant assessment systems for these habitats (Kelly, 2013) and there are very few studies focusing on the evaluation of ecological potential assessment of reservoirs based on benthic diatoms (Novais et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…abiotic spatial factors and catchment variables as landuse and hydromorphology (Gottschalk and Kahlert, 2012), physical and chemical quality of substratum Michelutti et al, 2003;Poulíčková et al, 2003Poulíčková et al, , 2004King et al, 2006;Ács et al, 2007;Bolla et al, 2010), light conditions (Kelly et al, 1998;King et al, 2006), seasonality (King et al, 2002(King et al, , 2006Bolla et al, 2010;Rimet et al, 2015), water chemistry (Hofmann, 1994;King et al, 2000;Schönfelder et al, 2002;Kitner and Poulíčková, 2003;Blanco et al, 2004;Ács et al, 2005;Stenger-Kovács et al, 2007;Jüttner et al, 2010;Gottschalk and Kahlert, 2012) and also other groups of organisms, such as indirect effect of fish (Blanco et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As such, they can provide a useful marker for detecting localised, short-to medium-term changes and patchiness at small spatial scales, for example, pollution resulting from the intermittent release of sewage, shoreline development, road works or salting (Hawes and Smith 1993;Passy 2001). Many studies have shown that diatoms from littoral areas can indicate major environmental gradients (Douglas and Smol 1995;King et al 2000;Lim et al 2001;Schönfelder et al 2002), and they are increasingly used to assess water quality and, in particular, to monitor eutrophication of lakes in agricultural and urban areas (King et al 2000;Schönfelder et al 2002;Kitner and Poulíčková 2003;Blanco et al 2004;Ács et al 2005;Stenger-Kovács et al 2007). Although routine monitoring using periphytic diatoms is less frequently applied in lakes than in rivers or streams, several indices based on littoral diatoms have now been developed (Hofmann 1994;Kelly et al 2006;Stenger-Kovács et al 2007).…”
Section: Introductionmentioning
confidence: 99%